Pengaruh Stres, Kerja Disiplin Kerja Dan Semangat Kerja Terhadap Kinerja Karyawan Ptpn XII Sumber Tengah Desa Silo, Kec.Silo Kab.Jember - Muhammad Fakri Arifin; Tamriatin Hidayah; Nely Supeni (Program Studi Manajemen, Sekolah Tinggi Ilmu Ekonomi Mandala, 2022)
This study aims to determine the partial and simultaneous influence of the variables of work stress, work discipline and work spirit on the performance of permanent employees of PTPN XII Sumber Tengah Desa.Silo, Kec. Silo Kab. Jember. The data used in this study were primary data in the form of data from questionnaires and secondary data in the form of vision and mission, values ​​and organizational structure which were obtained directly from PTPN XII Sumber Tengah Silo Village, Silo District, Jember Regency. The data processing method in this study uses the Research Indicator Test Analysis method, namely Validity Test and Reliability Test, Classical Assumption Test, namely Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test, Multiple Linear Regression, Coefficient of Determination Analysis and Hypothesis Testing, namely t-test and test F, with the help of SPSS 20 analysis tool. The results showed that the variables of work stress and work morale partially had no significant and positive effect on the performance of employees of PTPN XII Sumber Tengah Silo Village, Kec. Silo Kab. Jember and the variable work discipline partially had a significant effect and positive on the performance of employees of PTPN XII Sumber Tengah Silo Village, Kec. Silo Kab. Jember, and simultaneously the variables of work stress, work discipline and work spirit affect the performance of employees of PTPN XII Sumber Tengah Desa. Silo, Kec Silo Kab. Jember